Experimental investigation on behaviour of cross-flow thermal effluent discharge in free surface flow - Ibrahim, Zulkiflee (Universiti Teknologi Malaysia, 2009)
Thermal discharges such as from power stations or industries into rivers causing degradation of water quality. A study was conducted in the laboratory to investigate the changes of the ambient temperature caused by thermal effluent discharged into the flow. A cross–flow thermal effluent is discharged from the bed of the channel. Thermal effluent flow rates of 0.133 liter/s and 0.05 liter/s and ambient flow rates of 20 liter/s and 10 liter/s were used in the study. Observation of thermal mixing process in the channel is concentrated in the near-field zone. The thermal dispersion patterns were observed along the channel through the isothermal lines; while the changes of ambient temperature are studied from the experimental data. The results indicate that the temperature changes are drastic in the near-field mixing zone. Then it gradually reduces along the channel until reaches the far-field mixing zone. Lower layer of the flow experiences high excess temperature compared to middle and upper layers of the flow. Meanwhile, larger effluent flow rate produces higher excess temperature in the receiving water body than small effluent flow rate. Based on experimental data, equations of excess temperature and dispersion were established